2021
DOI: 10.1128/jcm.02486-20
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Saliva Specimens for SARS-CoV-2 Testing

Abstract: We evaluated saliva (SAL) specimens for SARS-CoV-2 RT-PCR testing by comparison of 459 prospectively paired nasopharyngeal (NP) or mid-turbinate (MT) swabs from 449 individuals with the aim of using saliva for asymptomatic screening. Samples were collected in a drive-through car line for symptomatic individuals (N=380) and in the emergency department (ED) (N=69). The percent positive and negative agreement of saliva compared to nasopharyngeal swab were 81.1% (95% CI: 65.8% – 90.5%) and 99.8% (95% CI: 98.7% – 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 26 publications
5
70
0
1
Order By: Relevance
“…Other studies have demonstrated the usefulness of pooled sample testing for evaluating saliva samples. [48][49][50] Because the demand for screening large numbers of people is increasing, we have started comparing the sensitivities of pooled-sample testing and individual testing at Keio University. The results of the pooled-sample testing are beyond the scope of this paper, and the results we describe in the following section were obtained from individual RT-qPCR testing.…”
Section: Sample Pooling For Sars-cov-2 Rt-qpcrmentioning
confidence: 99%
“…Other studies have demonstrated the usefulness of pooled sample testing for evaluating saliva samples. [48][49][50] Because the demand for screening large numbers of people is increasing, we have started comparing the sensitivities of pooled-sample testing and individual testing at Keio University. The results of the pooled-sample testing are beyond the scope of this paper, and the results we describe in the following section were obtained from individual RT-qPCR testing.…”
Section: Sample Pooling For Sars-cov-2 Rt-qpcrmentioning
confidence: 99%
“…However, saliva has been used during the COVID-19 pandemic because of the high sen-sitivity and the ease of specimen collection [20,21,23]. Barat et al has evaluated pooled saliva testing using a MBTE platform for TNA extraction [11]. In our current study, we showed that the benefit of the LRE was most notable for pooled saliva specimens, in which the positive rate was higher for LRE than that of MBTE (88.3% vs. 81.7%).…”
Section: Comparison With Other Studiesmentioning
confidence: 49%
“…During the COVID-19 pandemic, large scale testing for SARS-CoV-2 has been implemented as one of the public health measures to identify patients for early treatment and isolation to prevent further transmission [3]. Because the current diagnostic capacity cannot cope with the large number of specimens, pooled testing has been advocated [11,19]. This study showed that the LRE automated system has similar performance for NPS and better performance for saliva than MBTE in pooled specimens.…”
Section: Conclusion and Implications For Clinical Practice And Research Studiesmentioning
confidence: 96%
See 2 more Smart Citations